The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1175/mwr-d-10-05037.1
|View full text |Cite
|
Sign up to set email alerts
|

A Large-Eddy Simulation Study of Moist Convection Initiation over Heterogeneous Surface Fluxes

Abstract: This study uses large-eddy simulations to investigate processes of moist convection initiation (CI) over heterogeneous surface fluxes. Surface energy balance is imposed via a 1808 phase lag of the surface moisture flux (relative to the sensible heat flux), such that the relatively warm surface is relatively dry (and the relatively cool surface is relatively wet). As shown in previous simulations, a mesoscale circulation forms in the presence of surface-flux heterogeneity, which coexists with turbulent fluctuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 65 publications
(91 reference statements)
3
66
0
Order By: Relevance
“…The redistribution of soil moisture increases the large-area heterogeneity, but decreases the small-area heterogeneity. This is in accordance with Adler et al (2011);Kang and Bryan (2011), who found an influence of redistribution of soil moisture on the location of convective inition. Therefore, area "blue", mainly containing small convective cells, is more influenced than area "red" with the large advected precipitation band.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The redistribution of soil moisture increases the large-area heterogeneity, but decreases the small-area heterogeneity. This is in accordance with Adler et al (2011);Kang and Bryan (2011), who found an influence of redistribution of soil moisture on the location of convective inition. Therefore, area "blue", mainly containing small convective cells, is more influenced than area "red" with the large advected precipitation band.…”
supporting
confidence: 92%
“…Despite to the systematic effect on partitioning of the heat fluxes, precipitation reacts less systematically on soil moisture variations Hohenegger et al, 2009). The distribution and inhomogeneity of soil moisture patterns may initiate secondary circulation (Clark et al, 2004;Adler et al, 2011;Kang and Bryan, 2011;Dixon et al, 2013;Maronga and Raasch, 2013;Froidevaux et al, 10 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Here we use the numerical model "Cloud Model version 1" (CM1) that has been used for several LES studies in recent years (e.g., Kang and Bryan 2011;Kang et al 2012;Wang 2014;Nowotarski et al 2014;Markowski and Bryan 2016). Details of the model used here, including a new "two part" subgrid model near the surface, are provided in the Appendix.…”
Section: Large-eddy Simulationsmentioning
confidence: 99%
“…Garcia-Carreras et al (2011) explained the reasons for a preferred location of shallow convective clouds on the front of the mesoscale circulations. Recently, Kang and Bryan (2011) studied the effect of the amplitude of the surface heterogeneity on the transition to deep convection by prescribing sinusoidal surface fluxes of various amplitudes. As the amplitude becomes larger the area of mesoscale convergence becomes narrower and stronger and will lead to an earlier transition to deep convection.…”
Section: Introductionmentioning
confidence: 99%